Factors influencing the occurrence of ischemic stroke in elderly patients with hypertension and type 2 diabetes mellitus: a case-control study - Chujun Li; Yuzhen Chen; Xiuli Ou; Tianhui You (BMC Neurology)
Abstract Objective To investigate the risk factors for ischemic stroke in elderly patients with hypertension and type 2 diabetes mellitus. Methods A total of 112 elderly patients with hypertension and type 2 diabetes, treated at Jiangmen Central Hospital from January 2023 to December 2023, were selected and categorized into a stroke group and a non-stroke group, each comprising 56 patients. The two groups were examined for demographic data, risk variables were evaluated by multifactorial logistic regression analysis, and the predictive value was determined using ROC curves. Results The comparison of hyperhomocysteinemia (HHcy), fibrinogen (FIB), and high-density lipoprotein cholesterol (HDL-C) between the non-stroke and stroke groups revealed statistically significant differences (P < 0.05). Logistic regression analysis indicated that HHcy (OR 16.936; 95% CI 1.946–146.071; P = 0.010), FIB (OR 1.773; 95% CI 1.238–2.540; P = 0.002), and HDL-C (OR 0.182; 95% CI 0.043–0.775; P = 0.021) were significant factors in the onset of ischemic stroke among elderly patients with hypertension and type 2 diabetes. ROC curve analysis revealed that the area under the curve (AUC) for FIB, HDL-C, and HHcy in diagnosing stroke associated with hypertension and type 2 diabetes mellitus in the elderly were 0.704, 0.640, and 0.598, respectively, while the AUC for the combined diagnosis of all three was 0.784. Conclusions HHcy, FIB, and HDL-C independently influence the occurrence of ischemic stroke in elderly patients with hypertension combined with type 2 diabetes mellitus, and their combined enhanced predictive capability for ischemic stroke occurrence.